ESTIMATION OF FISHING MORTALITY AND MIGRATION COEFFICIENT OF THE FISHERY OF JUVENILE MACRO BRACHIUM ROSENBERG/I FROM KALU RIVER IN MAHARASHTRA - BIRADAR, R. S.; VENKATESHVARAN, K. (Journal of Indian Fisheries Association, 2015)
The freshwater prawn, Macrobrachium rosenbergii breeds in estuaries and the juveniles after completion of their larval stage start their upward migration towards rivers. It is at this stage fishing of juveniles takes place in river mouths. In this study fishing mortality and migration coefficients of juvenile fishery of M. rosenbergii from a natural habitat of Kalu river near Titwala, in Maharashtra are estimated based on data presented by Indulkar and Shirgur (1995) for 1991 and 1992 fishing seasons. The fishing mortality was estimated to be 1.50 and 1.28 for a fishing season of 3 months in 1991 and 1992 respectively, while the migration coefficient was computed to be 3.53 during the fishing season. As the average exploitation rate during the study period was only 0.24, the juveniles are not heavily fished and there is a scope for almost doubling the present catch to about 4 million seeds per fishing season. Keywords : Fishing mortalities, Migration coefficient, Exploitation rate.